Polish-German preschoolers develop and use heritage Polish differently depending on whether they heard German from birth or not - De Houwer, Annick (Frontiers in Psychology, 2023)
This study assessed the language proficiency and use of a hitherto under-investigated group, viz., 3.5-year-olds growing up with Polish as a heritage language and German as societal language. All children (N = 28) heard Polish from birth in the home but half the children also heard German from birth (Bilingual First Language Acquisition, BFLA) while the other half added German through preschool (Early Second Language Acquisition, ESLA). All children attended German preschools. Data collection relied on an online survey filled out by 28 mothers and 20 fathers. There were large discrepancies between parental answers to general versus detailed questions regarding language use (choice) amongst parents and children. This has important repercussions for much of questionnaire based bilingualism research. Children were developing productive language as expected but BFLA preschoolers spoke German better or spoke both languages equally well whereas ESLA preschoolers spoke Polish better. Apart from BFLA children’s much longer and daily exposure to German from birth, these BFLA-ESLA differences in relative Polish proficiency may relate to different current patterns of language choice, with (1) Polish less present in parent–child interactions involving BFLA than ESLA preschoolers, and with (2) BFLA but not ESLA preschoolers mostly hearing Polish from just a single parent. The BFLA-ESLA difference thus made a difference to children’s heritage Polish development and use already at age 3.5.